The effect of mental fatigue on the accuracy of the direct free kick in terms of some kinematic variables for football players - Alkhawaldeh, I. M. (Asian Journal of Sports Medicine, 2023)
Background: Mental fatigue is one of the phenomena associated with the skillful sports performance of football players. There is a link between mental fatigue and the quality of skillful performance. It occurs during or after a mental activity, which is reflected in a decrease in physical fitness and a reduction in the ability to focus. Objectives: This study was designed to find the association between mental fatigue and skill performance by inferring the kinematic variables. Sports skills demand excellent performance that is connected to mindfulness. Mental weariness impacts a person`s ability to perform physically and skillfully in a sport, especially if that performance requires high accuracy and intensity. Methods: The empirical research consisted of 24 players specializing in direct free kicks. Test for the accuracy of free kick shooting, a mental fatigue experiment, and a re-test of direct free kick shooting was performed and analyzed through Kinovea 0.9.5 software. Results: The mean difference in the fatigue level of players before and after concerning the kinematic variables among football players was found to be statistically significant (P-value < 0.001). Conclusions: The study recommended developing programs that support the mental stability of the player during matches to be able to continue the required skill performance, no matter how much mental fatigue he is exposed to, which occurs as a result of several circumstances during football matches.